PATTERN OF SEMIOTIC REASONING IN SOLVING TWO-DIMENSIONAL SHAPE PROBLEMS: A MULTIMODAL ANALYSIS - Ekowati, Dyah Worowirastri; Yayuk, Erna; Restian, Arina (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2023)
The process of drawing conclusions in semiotic reasoning based on objects, signs, students' interpretation of the meaning of signs is reflected through written, verbal, and gestural answers (multimodal). Therefore, this research aims to describe the patterns of students' semiotic reasoning in solving two-dimensional shape problems based on a multimodal analysis. This study was conducted qualitatively using an exploratory descriptive approach. The research was conducted by involving two participants from the third grade of Muhammadiyah Elementary School (MES), Malang. The instruments used were observations, interview guidelines, and written exam questions. Observations were made when the participants solved problems in writing and during interviews. The interviews were conducted to confirm the written answers. The written test consisted of one question about the perimeter of a two-dimensional shape. The research results of the two third-grade students were analyzed using four stages of data transcription, sorting and selecting appropriate data, data presentation, and drawing conclusions. The research obtained two patterns of semiotic reasoning used by the participants. The first pattern was analysis, analysis-generalization, integration, and justification. The second pattern was analysis, analysis-generalization, integration, analysis, integration, integration, and justification. In addition, it was found that the first pattern gave the wrong final answer. In the first pattern, especially at the stage of implementing the problem-solving plan, the participant made a mistake in the integration indication, resulting in a wrong answer. Follow-up research needs to be carried out to determine the quality of students' reasoning ability when solving multimodal-based mathematical problems.